The term structure of interest rates when the growth rate is unobservable - Frank Riedel (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
The effect of incomplete information on the term structure of interest rates is examined in the framework of a pure exchange economy under uncertainty. When the growth rate of the aggregate endowment is known, the term structure is flat and deterministic. When agents do not observe the (constant) growth rate, interest rates are stochastic and the term structure turns out to be linearly decreasing. As a possible explanation of this astonishing fact, we suggest that rational and risk-averse investors consider long-term bonds as a good hedge against unfavorable realizations of the growth rate.
urn:nbn:de:kobv:11-10064620
Keywords: D5; D9; E4; G1; 330; Term Structure of Interest Rates; Incomplete Information